Evidence and expert consensus based German guidelines for the use of repetitive transcranial magnetic stimulation in depression. (28th May 2022) - Hebel, Tobias; Grözinger, Michael; Landgrebe, Michael; Padberg, Frank; Schecklmann, Martin; Schlaepfer, Thomas; Schönfeldt-Lecuona, Carlos; Ullrich, Heiko; Zwanzger, Peter; Langguth, Berthold; ,; Bajbouj, Malek; et al.
Abstract: Introduction: Non-invasive brain stimulation techniques such as repetitive transcranial magnetic stimulation (rTMS) offer a promising alternative to psychotherapeutic and pharmacological treatments for depression. This paper aims to present a practical guide for its clinical implementation based on evidence from the literature as well as on the experience of a group of leading German experts in the field. Methods: The current evidence base for the use of rTMS in depression was examined via review of the literature. From the evidence and from clinical experience, recommendations for the use of rTMS in clinical practice were derived. All members of the of the German Society for Brain Stimulation in Psychiatry and all members of the sections Clinical Brain Stimulation and Experimental Brain Stimulation of the German Society for Psychiatry, Psychotherapy, Psychosomatics and Mental Health were invited to participate in a poll on whether they consent with the recommendations. Findings: Among rTMS experts, a high consensus rate could be identified for clinical practice concerning the setting and the technical parameters of rTMS treatment in depression, indications and contra-indications, the relation of rTMS to other antidepressive treatment modalities and the frequency and management of side effects.